Phase III Study of Pemetrexed in Combination With Cisplatin Versus Cisplatin Alone in Patients With Malignant Pleural Mesothelioma. Issue 12 (20th April 2023) - Vogelzang, Nicholas J.; Rusthoven, James J.; Symanowski, James; Denham, Claude; Kaukel, E.; Ruffie, Pierre; Gatzemeier, Ulrich; Boyer, Michael; Emri, Salih; Manegold, Christian; Niyikiza, Clet; Paoletti, Paolo
Abstract : PURPOSE: Patients with malignant pleural mesothelioma, a rapidly progressing malignancy with a median survival time of 6 to 9 months, have previously responded poorly to chemotherapy. We conducted a phase III trial to determine whether treatment with pemetrexed and cisplatin results in survival time superior to that achieved with cisplatin alone. PATIENTS AND METHODS: Chemotherapy-naive patients who were not eligible for curative surgery were randomly assigned to receive pemetrexed 500 mg/m 2 and cisplatin 75 mg/m 2 on day 1, or cisplatin 75 mg/m 2 on day 1. Both regimens were given intravenously every 21 days. RESULTS: A total of 456 patients were assigned: 226 received pemetrexed and cisplatin, 222 received cisplatin alone, and eight never received therapy. Median survival time in the pemetrexed/cisplatin arm was 12.1 months versus 9.3 months in the control arm ( P = .020, two-sided log-rank test). The hazard ratio for death of patients in the pemetrexed/cisplatin arm versus those in the control arm was 0.77. Median time to progression was significantly longer in the pemetrexed/cisplatin arm: 5.7 months versus 3.9 months ( P = .001). Response rates were 41.3% in the pemetrexed/cisplatin arm versus 16.7% in the control arm ( P < .0001). After 117 patients had enrolled, folic acid and vitamin B12 were added to reduce toxicity, resulting in a significant reduction in toxicities in the pemetrexed/cisplatin arm. CONCLUSION: Treatment with pemetrexed plus cisplatin and vitamin supplementation resulted in superior survival time, time to progression, and response rates compared with treatment with cisplatin alone in patients with malignant pleural mesothelioma. Addition of folic acid and vitamin B12 significantly reduced toxicity without adversely affecting survival time.